PERANCANGAN DRAF PROSEDUR KERJA DAN INSTRUKSI KERJA PEMUSNAHAN BERKAS REKAM MEDIS TERKAIT DENGAN PELAKSANAAN SMM ISO 9001:2008 DI PUSKESMAS DANUREJAN II YOGYAKARTA - , SITI MUNAWWIROTUN N, Dra. Rawi Miharti, MPH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: The health center as a spearhead implementation of health measures, is responsible for coordinating and implementing comprehensive health development and integrated in their working area. Thus, in the era of globalization in which the free and rigorous competition, the need for certification of an increase in the quality of health services at the health center in order to meet the demands of QMS ISO 9001: 2008. The existence of the working procedures and work instructions Danurejan II service in the health center of Yogyakarta be written reference implementation of health services at the health center. Every health personnel who work in accordance with professional standards, standard operating procedures, service standards, professional ethics, respect the patient's right, put the interests of patients and General fire safety. Work procedures and work instructions including one of the requirements of ISO 9001:2008 QMS documentation to be written evidence in the implementation of health care. Goals: draft design working procedures and work instructions extermination medical record file associated with the implementation of ISO 9001:2008 QMS in PHC Danurejan II Yogyakarta. Methods Design: The designer uses the design concept is based on the theory that Syamsi retrieve data, know how to work, analyzing the work, establish how the bar, pouring into the workbook and put into the user guide. Results: Based on the results obtained, it can be peracang for design work procedures and work instructions that work procedures extermination medical record file and work instructions comprising instructions for committee work team building depreciation, depreciation operating instruction file medical records, work instructions extermination team building, Instruction work sorting files medical records, work instructions list the medical record file descriptions, work instructions extermination medical record files, news-making work instructions annihilation events.